The Influence of Self-Confidence on Mathematics Final Exam Scores of Students - Ndumadi, La; Bey, Anwar; Arvyaty; Zulfaidil (Jurnal Amal Pendidikan, 2024)
Self-confidence plays a significant role in students' academic performance, particularly in subjects such as mathematics, which can be challenging for many. Previous studies suggest that students who feel more confident in their abilities tend to perform better, as they are more likely to engage with the material, approach problems positively, and persist through difficulties. However, the relationship between self-confidence and academic achievement, especially in mathematics, remains inconclusive, with some studies reporting strong correlations and others finding minimal impact. This study aims to explore the levels of self-confidence among Class X Science students and examine how it relates to their mathematics exam scores. Using an Ex Post Facto method, 173 students were selected through purposive sampling. Descriptive analysis showed an average exam score of 73.28, with significant variation in student performance. Pearson correlation results indicated a low positive correlation between self-confidence and mathematics exam scores, though it was not statistically significant at the 0.05 level. The coefficient of determination (R Square) of 4.2% suggests that self-confidence contributes only slightly to the variance in mathematics results. In conclusion, while many students exhibit high self-confidence and perform reasonably well in mathematics, its impact on their academic performance is limited. Further research with a larger sample size and additional factors is recommended to gain a deeper understanding of this relationship